Design of a Real-Time Face Detection Parallel Architecture Using High-Level Synthesis. (24th December 2008) - Farrugia, Nicolas; Mamalet, Franck; Roux, Sébastien; Yang, Fan; Paindavoine, Michel
Abstract : We describe a High-Level Synthesis implementation of a parallel architecture for face detection. The chosen face detection method is the well-known Convolutional Face Finder (CFF) algorithm, which consists of a pipeline of convolution operations. We rely on dataflow modelling of the algorithm and we use a high-level synthesis tool in order to specify the local dataflows of our Processing Element (PE), by describing in C language inter-PE communication, fine scheduling of the successive convolutions, and memory distribution and bandwidth. Using this approach, we explore several implementation alternatives in order to find a compromise between processing speed and area of the PE. We then build a parallel architecture composed of a PE ring and a FIFO memory, which constitutes a generic architecture capable of processing images of different sizes. A ring of 25 PEs running at 80 MHz is able to process 127 QVGA images per second or 35 VGA images per second.